Associação entre determinantes em saúde e ocorrência de casos humanos de leptospirose em Minas Gerais: um estudo ecológico 2010-2019 - Victor Melo Pereira (2023)
Introduction: Leptospirosis is considered a public health problem with great social and economic impact. The disease was cited as doubly omitted, since it is already classified in the international literature as a neglected tropical disease (NTD), it still has low government attention. This fact may be associated with the illness caused by this disease, which mostly affects the poor and marginalized portion of society. Objectives: This study aims to evaluate the association between health determinants and the illness from leptospirosis in the municipalities of the state of Minas Gerais from 2010 to 2019. Methodology: This is an ecological study and the units of analysis were the 853 municipalities in the state of Minas Gerais. Non-nominal aggregated secondary data between the years 2010 and 2019 were used. The Negative Binomial Model with Zero Inflation was used as a multivariate analysis technique, considering the incidence of leptospirosis in 2016 as the outcome and the IMRS indicators of 2016 or on a date closest available as explanatory variables Results: The results of the multiple model showed that the factors that remained associated with the incidence of leptospirosis were the Health, Education, Income and Employment indexes and the Urban Infrastructure variable. According to the estimated coefficients, the IMRS health index was associated with an increased incidence of leptospirosis. On the other hand, the other factors – education, income and employment index and the urban infrastructure variable – were associated with lower rates of the disease, thus acting as protective factors against illness. Conclusion: There is a strong association between leptospirosis and poverty in the state of Minas Gerais. Investment in urban infrastructure and guaranteeing favorable sanitary conditions for the population, as well as improving the dissemination of information and education would reduce the impact of the disease on the poor and underserved population. Descriptors: Social Determinants of Health; Zoonosis Surveillance; Leptospirosis, Social Vulnerability, Ecological Studies.